2021
DOI: 10.17485/ijst/v14i3.1178
|View full text |Cite
|
Sign up to set email alerts
|

Biochar and compost-based phytoremediation of crude oil contaminated soil

Abstract: Objectives: To study the effect of compost and biochar on phytoremediation of crude oil-contaminated soil. Methods: An attempt was made to remediate crude oil contaminated soil, using the phytoremediation method. The soil was amended with biochar and compost. Initially, the pH, moisture content and C/N ratio of the soil and amendments were determined. A pot culture experiment was conducted to study the effect of the amendments on the degradation of the Total Petroleum Hydrocarbons (TPH) in the crude oil contam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In general, the negative effect of TPH and TPH 1, observed in the physiological variables (height, and root, aerial and total dry biomass) is attributed to the inhibition caused by the increase in the different concentrations of hydrocarbons in the soil, which suppress the nutrient's availability (Cartmill et al, 2014;Ruley et al, 2019;Omara et al, 2020) and delay the water absorption by plants (Wang et al, 2013;Ruley et al, 2020;Deebika et al, 2021). Likewise, oil hydrocarbons alter the physical properties of soils such as permeability, in addition to suffocating roots, especially in fine-textured (clay) or shallow soils, affecting plant growth (Akinwumi et al, 2014;Grifoni et al, 2020;Ostovar et al, 2021).…”
Section: Results and Discussion Effect On The Plant Total Dry Biomassmentioning
confidence: 99%
“…In general, the negative effect of TPH and TPH 1, observed in the physiological variables (height, and root, aerial and total dry biomass) is attributed to the inhibition caused by the increase in the different concentrations of hydrocarbons in the soil, which suppress the nutrient's availability (Cartmill et al, 2014;Ruley et al, 2019;Omara et al, 2020) and delay the water absorption by plants (Wang et al, 2013;Ruley et al, 2020;Deebika et al, 2021). Likewise, oil hydrocarbons alter the physical properties of soils such as permeability, in addition to suffocating roots, especially in fine-textured (clay) or shallow soils, affecting plant growth (Akinwumi et al, 2014;Grifoni et al, 2020;Ostovar et al, 2021).…”
Section: Results and Discussion Effect On The Plant Total Dry Biomassmentioning
confidence: 99%
“…Many studies have reported successful implementation of biochar, microbiological inocula, urea, compost, etc. [61][62][63][64][65][66]. Various biosurfactants (BS) have recently received considerable attention as bioremediation-promoting agents [67][68][69].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these organic and inorganic modifiers increase phytoremediation efficiency by stimulating microorganisms' activities, increasing plant growth and biomass production (Clemente et al, 2012;Barati et al, 2018;Roohi et al, 2020;Boorboori and Zhang, 2022b). The Frontiers in Environmental Science frontiersin.org following are some of the most important modifiers used in recent years: poultry droppings, cow dung, biochar, rice husk, compost, technocell, steel slag, carbon materials (CMs), and nanomaterials (NMs) (Singh and Lee, 2016;Forján et al, 2018;Lebrun et al, 2021a;Deebika et al, 2021), and in the following, biochar's role in phytoremediation of HMs will be discussed in more detail.…”
Section: Phytoremediation Efficiency Plant Type and Other Factorsmentioning
confidence: 99%
“…Phytoremediation can be improved with biochar due to its long-term stability compared to other organic amendments as well as its effective role in improving the soil's physical, chemical, and biological properties (Cárdenas-Aguiar et al, 2019;Ratnasari et al, 2020). By improving soil pH, carbon content, soil aeration, soil fertility, water retention capacity, microbial diversity, and plant growth, biochar is highly effective at cleaning environments contaminated with HMs (Forján et al, 2018;Gong et al, 2019;Deebika et al, 2021). Furthermore, Its high specific surface area, porous structure (macropores and micropores), cation exchange capacity, and active functional groups make biochar an effective tool for stabilizing soil pollution and reducing HMs bioavailability for organisms (Song et al, 2016;Yang et al, 2017a;Zhang et al, 2019a).…”
Section: Biochar and Phytoremediationmentioning
confidence: 99%
See 1 more Smart Citation